Immunochemical Methods in Health Risk Assessment: Cross Reactivity of Antibodies against Mycotoxin Deoxynivalenol with Deoxynivalenol-3-glucoside - Ruprich, Jiří; Ostrý, Vladimír (Central European Journal of Public Health, 2008)
Co-occurrence of deoxynivalenol (DON) with other DON derivatives/metabolites and other Fusarium toxins, including zearalenone, nivalenol and as well as other mycotoxins (e.g. fumonisins) is frequently observed in food and feed. DON-3ß-glucopyranoside (DON-3-glucoside) was described as detoxification product of DON in wheat. This mycotoxin conjugate was observed in maize, barley, malt, beer and wort. Digestion of this conjugate in intestine is still unclear but due to possibility to release DON after hydrolysis is considered as potential masked mycotoxin. DON is analytically quantified by various methods and also with immunochemical methods. There is no available information about specificity of anti-DON antibodies used in commercial ELISA kits with DON-3-glucoside. Preliminary testing of anti-DON monoclonal antibodies used in ELISA kits RIDASCREEN®DON (R-Biopharm AG, Germany) approved a hypothesis that these antibodies have high relative cross reactivity with DON-3-glucoside. In two repeated tests cross reaction 82 and 98% were observed. Analytical results produced by these ELISA kits can be interpreted as an approximate sum of both mycotoxins. Described cross reactivity can lead to overestimating of DON concentration. Over these cross reactions immunochemical methods are mentioned still valuable for quantitative screening and even for an initial exposure assessment in situations when there are practical or economical reasons not to use another analytical method with a reasonable low limit of quantification (< 50 ppb).
Keywords: Data Interpretation, Statistical; Trichothecenes; Antibodies, Monoclonal; hodnocení rizik; Mycotoxins; Risk Assessment; Enzyme-Linked Immunosorbent Assay; Cross Reactions; ELISA; mykotoxiny; Fusarium; trichotheceny; interpretace statistických dat; Immunoassay; imunoanalýza; imunochemie; Immunochemistry; monoklonální protilátky; zkřížené reakce